Arctic PASSION - Polar Monthly Mean Ice Surface Temperature (AP-MMIST) for the time period 1982 to 2024 - Gorm Dybkjær; Magnus Barfod Suhr; André Emil Toft Jensen; Suman Singha (PANGAEA, 2025)
The Arctic PASSION Polar Monthly Mean IST data set (AP-MMIST) is a combined surface temperature product covering open ocean, marginal ice zone and closed sea ice areas, represented by Sea Surface Temperatures (SST), Marginal Ice Zone Temperatures (MIZT) and sea Ice Surface Temperatures (IST). Beside ocean and sea ice the data set also includes surface temperatures from the Greenland and Antarctic ice sheets. AP-MMIST has been jointly developed and produced by Arctic PASSION WP-1 and the Sea Ice Thematic Assembly Centre (Sea Ice TAC) under the Copernicus Climate Change Service (C3S - service contract: 2022/C3S2_312b_MOi_SC1). The AP-MMIST is a monthly averaged temperature product based on the C3S daily IST CDR and ICDR level 3 data. The daily mean C3S IST data set is a resampled and averaged daily mean IST product using Global Area Coverage - Advanced Very High-Resolution Radiometer (AVHRR) IST level 2 data as input. The level 2 and 3 CDR and ICDR data records are described in Algorithm Theoretical Baseline Document (Eastwood et al., 2023). The surface temperature retrieval algorithm used to produce the basic level 2 product is a traditional split window algorithm using two Thermal InfraRed (TIR) channels to compensate for atmosphere and angular emissivity dependency. This is described in the Algorithm Theoretical Baseline Document (Eastwood et al., 2023). The level 1 TIR input data set is the full data record from the AVHRR on-board NOAA satellite platforms since 1982, as well as AVHRR records on-board Metop satellites since 2006. The product output format is NetCDF with standard attributes, following CF convention to the degree possible. The monthly data are divided into 2 monthly files, one for each hemisphere, SH and NH.